Effects of Artemisinin on Peak Sodium Current in Ventricular Myocytes - Song, Huanqiu; Ao, Zhuo; Song, Yuqin; Li, Xiang; Xu, Xue; Cheng, Cheng; Shi, Maojing; Liu, Lihua; Wu, Jiatong; Liu, Yuansheng; Han, Dong (Cardiology and Cardiovascular Medicine, 2020)
Background: Previous studies have confirmed that artemisinin can prevent arrhythmia by inhibiting K+ currents. Recent findings have shown that artemisinin attenuates sodium current in nodose ganglion and endocrine cells of rats. This study investigated the effects of artemisinin on peak sodium current in ventricular myocytes. Methods: Rat ventricular myocytes were isolated by Langendorff reverse aortic perfusion method. Peak sodium current was recorded using the whole-cell patch clamp technique. Results: The INa was reduced by 50 μM artemisinin, and the steady-state activation and inactivation curves were shifted toward the left. The time constant τ of the steady-state recovery curve increased from 2.89 ms to 7.13 ms. Conclusions: Artemisinin attenuates INa by modulating the voltage dependence of the Na+ channel similar to the class I anti-arrhythmia agents.